Augmented Reality in STEM Education: A Systematic Review of Cognitive, Affective, Psychomotor Outcomes - Prelia Dwi Amanah; Gian Aphrodita Emawa; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2023)
This study aims to map publication trends, thematic structures, and the representation of cognitive, affective, and psychomotor learning outcomes in AR research within STEM education through bibliometric analysis. Data were retrieved from the Dimensions.ai database using the keywords augmented reality, STEM education, cognitive, affective, and psychomotor outcome for publications published between 2013 and 2022, yielding 14,362 documents that were analyzed using VOSviewer. The results indicate a substantial increase in publications during 2020–2021, with book chapters representing the dominant document type (73.06%), whereas journal articles accounted for only 3.84%. Information and Computing Sciences and Biomedical and Clinical Sciences were the leading research fields; SDG 4 (Quality Education) and SDG 3 (Good Health and Well-Being) were the most frequently addressed SDGs. Network visualization identified 86 keywords organized into 4 major thematic clusters: cognitive, affective-pedagogical, psychomotor-system, and learner outcomes, with student, outcome, and skill emerging as the most central nodes. AR research in STEM education remains dominated by non-journal publications and has rarely integrated the simultaneous assessment of the three learning domains. These findings highlight the need for more empirical journal-based studies that explicitly evaluate cognitive, affective, and psychomotor learning outcomes, advancing the development of more valid and standardized psychomotor assessment instruments.